Heterogeneity and Persistence in Returns to Wealth - Fagereng, Andreas; Guiso, Luigi; Malacrino, Davide; Pistaferri, Luigi (Econometrica, 2020)
We provide a systematic analysis of the properties of individual returns to wealth using 12 years of population data from Norway's administrative tax records. We document a number of novel results. First, individuals earn markedly different average returns on their net worth (a standard deviation of 22.1%) and on its components. Second, heterogeneity in returns does not arise merely from differences in the allocation of wealth between safe and risky assets: returns are heterogeneous even within narrow asset classes. Third, returns are positively correlated with wealth: moving from the 10th to the 90th percentile of the net worth distribution increases the return by 18 percentage points (and 10 percentage points if looking at net‐of‐tax returns). Fourth, individual wealth returns exhibit substantial persistence over time. We argue that while this persistence partly arises from stable differences in risk exposure and assets scale, it also reflects heterogeneity in sophistication and financial information, as well as entrepreneurial talent. Finally, wealth returns are correlated across generations. We discuss the implications of these findings for several strands of the wealth inequality debate.